Hidup Bugar Cegah Menopause Dini (HarMoni): Optimalisasi Meningkatkan Kesehatan Reproduksi Perempuan - Veronica Yeni Rahmawati; Jehan Puspasari; Azwar; Muhammad Fiqriansyah; Fani Nurul Hidayah (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
Menopause is a natural process that occurs in all women, marked by the permanent cessation of menstruation (menstruation). Menopausal women experience physical changes that can affect their psychological condition. The purpose of this community service activity is to increase mothers' awareness in maintaining their reproductive health through providing education on Living Fit to Prevent Early Menopause (HarMoni). This activity was attended by PKK mothers and representatives of health cadres in the Mangga Dua Selatan Subdistrict, Central Jakarta. The methods used in this activity were a pre-test, interactive education, demonstration of fitness exercise movements, discussions about women's health and a post-test. The results of this community service activity showed an increase in participants' knowledge before and after the educational activity, participants who had good knowledge in the pre-test results were 13 people (61.9%) increased by 20 people (95.2%) in the post-test results. In conclusion, providing education through interactive education and open discussion methods has been proven effective in increasing mothers' knowledge about maintaining reproductive health through a healthy lifestyle, adequate rest, and light physical activity.